Mūla Maṅʻʺ kvanʻʺ Jetavanʻ Cha rā toʻ Bhu rāʺ krīʺ reʺ sāʺ cī raṅʻ toʻ mū so Vipassanā ñāṇʻ cañʻ kyamʻʺ krīʺ - Nārada, Jetavanʻ Cha rā toʻ Ūʺ, 1869-1955 (Haṃsāvatī Piṭakatʻ Puṃ nhipʻ tuikʻ, 1949)
Treatise on vipaśyana, a form of Buddhist meditation, according to the Maṅʻʺ kvanʻʺ method.